1984
DOI: 10.1002/kin.550160703
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the shock induced thermal decomposition of n‐propylsilane

Abstract: The kinetics and mechanism of the thermal decomposition of n-propylsilane have been studied by the single pulse shock tube-comparative rate technique a t pressures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 11 publications
(3 reference statements)
2
9
0
Order By: Relevance
“…This can be interpreted in terms of a normal deuterium isotope rate effect for methylsilane of about 10-20%. This is also in fairly good agreement with our shock-tube results [2].…”
Section: Primary Dissociation Process Observationssupporting
confidence: 92%
“…This can be interpreted in terms of a normal deuterium isotope rate effect for methylsilane of about 10-20%. This is also in fairly good agreement with our shock-tube results [2].…”
Section: Primary Dissociation Process Observationssupporting
confidence: 92%
“…The results from the pyrolysis of monomethylsilane showed that, out of the three elimination channels, i.e., 1,1-H 2 , 1,2-H 2 , and CH 4 elimination, the dissociation yield to eliminate CH 4 only accounted for 6%. 31,34,35 According to Haas and Ring, 35 the reaction of :SiH 2 with C 2 H 2 forms silylacetylene (HCCSiH 3 ) either by direct insertion of:SiH 2 into a C-H bond or by addition to the C-C triple bond to form silacyclopropene. In order to determine the main contributor to the formation of methane, we calculated the amount of methane produced when using 4.0 Torr of TriMS.…”
Section: A Formation Of Methane and Other Small Hydrocarbon Moleculesmentioning
confidence: 99%
“…Ethene 31,34,36-38 and propene 31,34 are known to be good free radical scavengers. Ethene 31,34,36-38 and propene 31,34 are known to be good free radical scavengers.…”
Section: Radical Recombination Reactionsmentioning
confidence: 99%
“…refs. 23,24) and molecular cleavage into methylsilane and methylsilanone, this reaction having its prototype in IR laser-induced decomposition of disiloxane H 3 SiOSiH 3 (ref. 25).…”
Section: Decomposition Mechanismmentioning
confidence: 99%